Strategies to enhance the benefits of exercise training in the respiratory patient - Hill, Kylie; Holland, A. (W B Saunders Co, 2014)
In people with chronic obstructive pulmonary disease, exercise training offered as part of pulmonary rehabilitation has strong evidence for increasing exercise capacity, reducing symptoms of dyspnea and fatigue, and improving health-related quality of life. Nevertheless, there is a proportion of people referred to pulmonary rehabilitation who achieve minimal gains, most likely because of profound ventilatory limitation during exercise or the presence of comorbid conditions that limit participation in exercise training. Several adjuncts or strategies have been explored to optimize the proportion of people referred to pulmonary rehabilitation who achieve significant and meaningful gains on program completion.